Analisis Strategi Relationship Marketing Pada Dimensi Social Benefit Pt. Bank Pembiayaan Rakyat Syariah (BPRS) Berkah Dana Fadhlillah Kabupaten Kampar - Yusriadi, Yusriadi (Sekolah Tinggi Ilmu Ekonomi Riau, 2023)
This research aims to analyze Relationship Marketing Strategy in the Social Benefit dimension of PT. Sharia People's Financing Bank (BPRS) Berkah Dana Fadhlillah Kampar Regency. With a total of 140 respondents, through descriptive analysis the results of the application of relationship marketing strategies in the social benefit dimension were high with an average score of 4.31 with the highest score being 4.46 with the statement